Combining Fluorescent Quantum Dots with Molecularly Imprinted Polymers for the Screening of both Emerging and Classical Environmental Pollutants: a Review - Zeb, Shakeel [UNESP]; Villa, Javier E. L.; Wong, Ademar [UNESP]; Khan, Sabir [UNESP]; Hussain, Sajjad; Sotomayor, Maria D. P. T. [UNESP] (Soc Brasileira Quimica, 2023)
Emerging and classical pollutants, such as antibiotics, pharmaceuticals, pesticides, dyes and heavy metals derived from human activity, currently pose serious threats to the environment and human health. Despite the grave danger posed by these pollutants, there is still no adequate monitoring of their presence in the environment. The regular determination of these contaminants in the environment can play a crucial role in the protection of human health and the preservation of ecosystems. New analytical techniques allow the reproducible quantification of analytes at very low concentration levels. Molecularly imprinted polymers (MIPs), with selective recognition, have also been combined with quantum dots (QDs) and suggested as valuable materials in the construction of optical sensors. Several strategies have been proposed for the selective detection of these pollutants in recent years. Rather than employing expensive, time-consuming standard analytical methods, fluorescent quantum dots coupled with molecularly imprinted polymers can be used for developing simple, rapid and highly selective analytical methods for the detection of these pollutants. This review presents a brief discussion on the application of tailor-made polymeric materials in tandem with quantum dots for the rational construction of efficient sensors capable of determining the presence of these pollutants in aquatic environments.
Keywords: quantum dots; molecular imprinting; fluorescence spectroscopy; core-shell nanomaterials